2006
DOI: 10.1079/ssr2005229
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy and germination in three Acacia (Fabaceae) species from central Argentina

Abstract: We studied dormancy and germination requirements of seeds of Acacia aroma, A. caven and A. furcatispina from a semi-arid region of central Argentina. Imbibition experiments were performed to determine the rate of water uptake in seeds. To determine optimal temperature for germination, seeds were incubated at three temperature regimes (15/5, 25/15 and 35/20°C) with a 12/12 h daily photoperiod or in total darkness. Additionally, differences in dormancy and germination in seed colour morphs of A. aroma were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
5
38
2
6
Order By: Relevance
“…(Seigler & Ebinger 2005), a perennial woody species belonging to the family Fabaceae, is an important component of the subtropical seasonal xerophytic forest of central Argentina (Giorgis et al 2011). Seeds of this species present PY due to a very thick and compact seed coat with a sclerified parenchyma (Funes & Venier 2006;Venier et al 2012a). It is not clear how this species breaks PY in nature, however previous studies suggested that passing through the digestive tract of cattle might break seed dormancy in this species (Venier et al 2012b) while fire and other native dispersal agents such as foxes might not be involved in this process (Ferreras et al 2015).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…(Seigler & Ebinger 2005), a perennial woody species belonging to the family Fabaceae, is an important component of the subtropical seasonal xerophytic forest of central Argentina (Giorgis et al 2011). Seeds of this species present PY due to a very thick and compact seed coat with a sclerified parenchyma (Funes & Venier 2006;Venier et al 2012a). It is not clear how this species breaks PY in nature, however previous studies suggested that passing through the digestive tract of cattle might break seed dormancy in this species (Venier et al 2012b) while fire and other native dispersal agents such as foxes might not be involved in this process (Ferreras et al 2015).…”
mentioning
confidence: 97%
“…Physical dormancy (hereafter, PY), one of the types of seed dormancy, is caused by one or more layers of palisade cells in the seed or fruit coat; such layers are impermeable to water and, once broken, dormancy cannot be reversed . Th is type of dormancy is most commonly found in species occurring in arid and semi-arid regions (Funes & Venier 2006;) and in fi re-prone areas, especially in species with a persistent seed bank (Ooi et al Acta Botanica Brasilica -31(1): 141-146. January-March 2017 2014; Liyanage & Ooi 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Para el total de especies estudiadas, el rango de temperatura óptimo para la germinación coincide con las temperaturas estivales, momento en el cual se producen las precipitaciones en el área de estudio. Patrones similares han sido reportados por Funes & Venier (2006), Gurvich et al (2008), Funes et al (2009) y Zalazar et al (2009, para distintas especies de la región chaqueña argentina. También se ha encontrado este patrón para especies de bosques y matorrales mediterráneos (Bell et al 1993, Bell 1994, Figueroa et al 1996, Turner et al 2005.…”
Section: Discussionunclassified